Du socle au paysage : essai pour un nouveau regard sur les reliefs - Claire Portal (Projets de Paysage)
This paper studies the geomorphic component of “landscapes artialisation” by studying the major landforms in landscapes’ representations. Landforms are considered here as landscapes patterns constituting the "geographical basement " for landscape painter, holding a cultural aspect emanating from a new field of research, cultural geomorphology. As patterns, landforms also participate in the pictorial and lyric composition of artistic works and show themselves as driving elements of the construction of western landscapes models.